Heparan sulphate sulphotransferase expression in mice and Caenorhabditis elegans. (1st April 2003) - Turnbull, J.; Drummond, K.; Huang, Z.; Kinnunen, T.; Ford-Perriss, M.; Murphy, M.; Guimond, S.
Abstract : Heparan sulphate (HS) acts as a multifunctional cell regulator, with specific sulphated saccharide sequences designed for selective interactions with many proteins. Functionally, these interactions result in regulation of the protein activities, and there is growing evidence that cells can dynamically alter the structure of HS sequences that they display. HS biosynthesis involves the action of a complex set of enzymes with polymerase, epimerase and sulphotransferase (ST) activities. In higher organisms, multiple isoforms of STs decorate the nascent HS chains with specific patterns of sulphation that confer selective biological functions. The study of HSSTs in model organisms provides a valuable opportunity to examine the expression of these enzymes in relation to the structure and activities of the HS produced. Here we describe that, in mice, there are stage-specific combinations of HSST isoenzymes that underlie the synthesis of different HS species at different times in the developing brain. This differential expression of HSSTs results in the synthesis of structurally variant HS species that form functional signalling complexes with specific fibroblast growth factors and their receptors. Regulated synthesis of specific HS species could be a mechanism for the regulation of proliferation and differentiation in the developing brain. We also describe evidence that a Caenorhabditis elegans orthologue of the mammalian 2OST enzyme, called HST-2, is essential for the normal development of this nematode. Together, these studies emphasize the importance of HSSTs in the biosynthesis of functionally variant HS proteoglycans, and demonstrate the importance of these complex regulatory molecules in developmental processes.